2016
DOI: 10.1080/13664530.2016.1185028
|View full text |Cite
|
Sign up to set email alerts
|

The experience of burnout among English language teachers in Iran: self and other determinants

Abstract: Burnout in teachers is an important concern since it adversely impacts their instruction as well as their psychological, mental, and physical health. The present study examined the levels of burnout (i.e. emotional exhaustion, depersonalization, and reduced personal accomplishment) experienced by Iranian English language teachers. Specifically, the relationships of participants' gender, workplace context, grade level taught, and teaching experience to their burnout were investigated. Data were collected from 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 49 publications
2
13
0
Order By: Relevance
“…The results of quantitative data analysis revealed that on the whole, there was a significant relationship between teachers' self-efficacy and their instructional practice irrespective of their discipline. These findings get support from those of previous studies (e.g., Artino, 2012;Gibson & Dembo, 1984;Guskey, 1988;Sadeghi & Khezrlou, 2014, 2016Woolfolk & Hoy, 1990). As Richards (2008) rightly notes, teachers' efficacy beliefs allude to and strengthen their classroom instructional practices.…”
Section: Discussionsupporting
confidence: 85%
“…The results of quantitative data analysis revealed that on the whole, there was a significant relationship between teachers' self-efficacy and their instructional practice irrespective of their discipline. These findings get support from those of previous studies (e.g., Artino, 2012;Gibson & Dembo, 1984;Guskey, 1988;Sadeghi & Khezrlou, 2014, 2016Woolfolk & Hoy, 1990). As Richards (2008) rightly notes, teachers' efficacy beliefs allude to and strengthen their classroom instructional practices.…”
Section: Discussionsupporting
confidence: 85%
“…It should be noted that prior to the pandemic, only some studies had explored the psychological well-being of teachers in language classrooms (e.g., Nagamine, 2018;M. Rezvani & S. Rezvani, 2017;Sadeghi & Khezrlou, 2016). Upon consideration of Maslach and Leiter's (2008) construct of burnout, a handful of studies had examined language teacher' exhaustion, depersonalization and reduced accomplishment.…”
Section: Résumémentioning
confidence: 99%
“…Upon consideration of Maslach and Leiter's (2008) construct of burnout, a handful of studies had examined language teacher' exhaustion, depersonalization and reduced accomplishment. In these studies, it was observed that overwhelming teaching conditions led to high levels of burnout, which in turn work to the detriment of language education among teachers and learners (Meidani et al, 2019;Sadeghi & Khezrlou, 2016).…”
Section: Résumémentioning
confidence: 99%
“…As indicated, the benefits of group work are many and its usage is proving to be an increasingly integral component of a well-rounded tertiary education. This belief is also considered so important by students since they stated that they believe group work to be valuable and to have many benefits (Lima, Carvalho, Assunção Flores, & Van Hattum-Janssen, 2007;Sadeghi & Khezrlou, 2014;Sadeghi & Khezrlou, 2016;Sadeghi, Khezrlou & Modirkhameneh, 2017). However, it is reported in the literature that for a number of students, group work can be an unpleasant and preferably avoidable element of study -primarily due to experi ences of working in dysfunctional groups (e.g., Aggrwal, O'Brien, 2008;Dommeyer, 2007;Pfaff & Huddleston, 2003).…”
Section: Attitudes Towards Group Workmentioning
confidence: 99%